Sintered silver colloid material and preparation method thereof

By preparing sintered silver glue materials containing components A and B, and sintering under low temperature and pressure-free conditions, the problem of difficult pressure-free silver glue forming a dense sintered structure is solved, and the high mechanical properties and stability of sintered silver glue materials are achieved.

CN119662174APending Publication Date: 2025-03-21HUNAN CHUANGJIN TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411911151.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

Pressure-free silver glue is difficult to form a dense sintered structure, which affects its mechanical properties, resulting in easy interface layering after aging test or impact test, resulting in failure of bonding and electrical connections.

Method used

By preparing sintered silver glue material including components A and components B, component A consists of silver powder filler, resin, modified PVB and diluent, component B consists of aromatic amine curing agent and accelerator, sintered under low temperature and pressure-free conditions to ensure the mechanical properties of the silver glue after sintering.

Benefits of technology

The sintered silver glue material sintered under low temperature and pressure-free conditions has good mechanical properties, high shear strength, low volume resistivity, and remains stable after aging and impact tests.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119662174A_ABST
    Figure CN119662174A_ABST
Patent Text Reader

Abstract

The invention provides a sintered elargol material and a preparation method thereof, and relates to the technical field of elargol, the sintered elargol material comprises a component A and a component B, the component A comprises the following preparation raw materials in parts by mass: 100 parts of silver powder filler, 5-13 parts of resin, 3-8 parts of modified PVB (Polyvinyl Butyral) and 0.2-2 parts of diluent; the component B comprises 100 parts of an aromatic amine curing agent and 0.1-1 part of an accelerant; the modified PVB is prepared from PVB and a modifier. The preparation method of the sintered silver colloid material comprises the following steps: S1, mixing flake silver powder, resin, an accelerant and a diluent to obtain a first mixture; s2, grinding the modified PVB and particle silver powder to obtain a second mixture; s3, mixing the first mixture and the second mixture, and filtering to obtain the component A. The sintered silver colloid material prepared by the invention has excellent stability and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of silver paste, and in particular relates to a sintered silver paste material and a preparation method thereof. Background Art

[0002] Conductive silver glue, an adhesive with conductive properties, is primarily composed of a base resin and a conductive filler (such as silver powder). After curing or drying, this material establishes a conductive path, enabling electrical connections between dissimilar materials. It plays a crucial role in the packaging and bonding of electronic components and assemblies, particularly in microelectronics assembly, where it is gradually replacing traditional soldering techniques.

[0003] In existing technology, pressed silver paste uses a hot pressing process to fill gaps, forming a tight conductive path, thereby improving the performance of the silver paste. However, this process is complex, requires high equipment requirements, and may damage electronic components during the pressure sintering process. In contrast, pressureless silver paste can adapt to electronic components of various shapes and sizes, providing greater flexibility in product design.

[0004] Despite this, pressureless silver paste struggles to form a dense sintered structure due to the lack of pressure, which compromises its mechanical properties. After aging or impact testing, pressureless silver paste is prone to interfacial delamination, leading to bonding and electrical connection failure. Therefore, despite the mechanical shortcomings of pressureless silver paste, it remains a technical challenge that needs to be addressed. Summary of the Invention

[0005] The present invention is to overcome the above technical problems and thus provides a sintered silver paste material and a preparation method thereof. The sintered silver paste material prepared by the present invention can be sintered under low temperature and pressureless conditions, and the sintered silver paste has good mechanical properties.

[0006] The present invention solves the above technical problems through the following technical solutions.

[0007] The present invention provides a sintered silver paste material, comprising component A and component B;

[0008] Component A includes the following raw materials in parts by weight: 100 parts of silver powder filler, 5 to 13 parts of resin, 3 to 8 parts of modified PVB and 0.2 to 2 parts of diluent;

[0009] Preferably, the component A comprises the following raw materials in parts by mass: 100 parts of silver powder filler, 7 to 11 parts of resin, 4 to 8 parts of modified PVB and 0.2 to 1.0 parts of diluent.

[0010] Component B includes the following raw materials in parts by weight: 100 parts of aromatic amine curing agent and 0.1 to 1 part of accelerator;

[0011] The raw materials for preparing the modified PVB include PVB (polyvinyl butyral, CAS No.: 63148-65-2) and a modifier; wherein the modifier is DOA or DEHA;

[0012] The silver powder filler includes flaky silver powder and granular silver powder; the granular silver powder is spherical silver powder or quasi-spherical silver powder.

[0013] In the present invention, the mass ratio of the component A: the component B is 100:5-15; preferably, the mass ratio of the component A: the component B is 100:8-10; for example, 100:9.

[0014] In the present invention, the modified PVB comprises the following raw materials in parts by mass: 100 parts of PVB and 10 to 35 parts of a modifier; preferably, the modified PVB comprises the following raw materials in parts by mass: 100 parts of PVB and 15 to 25 parts of a modifier.

[0015] In the present invention, the modified PVB is composed of the following raw materials in parts by mass: 100 parts of PVB, 10 to 35 parts of a modifier, and 150 to 250 parts of DMF; preferably, the modified PVB is composed of the following raw materials in parts by mass: 100 parts of PVB, 15 to 25 parts of a modifier, and 180 to 230 parts of DMF.

[0016] In the present invention, the preparation method of the modified PVB is to mix PVB and a modifier, heat, degas, and dry;

[0017] Wherein, the heating temperature is 85-95°C; the heating time is 15-30 minutes;

[0018] The degassing process is to let it stand for 20 to 50 minutes, for example, 30 minutes;

[0019] The drying process is vacuum drying at 100-130° C. for 3-5 hours.

[0020] In the present invention, PVB is usually used as an organic carrier, and the modified PVB has better physical stability than PVB. The modifier enables PVB to have better resistance to deformation, thereby improving the overall durability of the silver glue material.

[0021] In the present invention, the butyraldehyde content of the PVB is 70-75%. The aldehyde content has a great influence on the mechanical properties of the modified PVB, and the toughening effect is most significant when the PVB contains 70-75% butyraldehyde.

[0022] In the present invention, the viscosity of the PVB is 15.0 to 18.0 mPa·s.

[0023] In the present invention, the resin comprises 70 parts by mass of bisphenol A epoxy resin and 20 to 40 parts by mass of polypropylene glycol diglycidyl ester resin; preferably, the resin comprises 70 parts by mass of bisphenol A epoxy resin and 25 to 36 parts by mass of polypropylene glycol diglycidyl ester resin.

[0024] In the resin formula of the present invention, polypropylene glycol diglycidyl ester resin is also added to the bisphenol A epoxy resin. The polypropylene glycol diglycidyl ester resin can reduce the viscosity of the standard resin and impart excellent elongation and impact resistance to the system. In addition, the polypropylene glycol diglycidyl ester resin is a bifunctional epoxy resin active diluent with low viscosity at room temperature. It can effectively reduce the viscosity of the silver glue, thereby improving its fluidity and operability.

[0025] Furthermore, the viscosity of the bisphenol A epoxy resin is 8000-12000 cps, preferably 8000-11000 cps.

[0026] Furthermore, the epoxy equivalent of the bisphenol A epoxy resin is 176 to 188 g / eq, preferably 176 to 184 g / eq.

[0027] Furthermore, the epoxy equivalent of the polypropylene glycol diglycidyl ester resin is 310 to 330 g / eq.

[0028] Furthermore, the viscosity of the polypropylene glycol diglycidyl ester resin is 55 to 75 cps.

[0029] In the present invention, the silver powder filler comprises 15 to 35 parts of granular silver powder and 55 to 75 parts of flaky silver powder in parts by mass; preferably, the silver powder filler comprises 15 to 20 parts of granular silver powder and 60 to 75 parts of flaky silver powder in parts by mass.

[0030] In the present invention, flaky silver powder, due to its flake or scale-like form, can provide more surface and line contact with the silver paste, thereby increasing the contact area and reducing resistivity. Granular silver powder, on the other hand, has better fluidity and coating properties, but due to its high surface energy, granular silver powder may agglomerate.

[0031] Furthermore, the D50 of the flaky silver powder is 1.0-4.0 μm.

[0032] Furthermore, the specific surface area of ​​the flaky silver powder is 0.2 to 0.5 m 2 / g.

[0033] Furthermore, the particle size of the granular silver powder is D50=0.1-0.4 μm, preferably D50=0.3 μm.

[0034] Furthermore, the specific surface area of ​​the granular silver powder is 0.80 to 1.2 m 2 / g.

[0035] The flaky silver powder used in this invention has a high tap density, which facilitates more efficient void filling within the conductive material, thereby creating a uniformly distributed conductive network. Furthermore, the inclusion of granular silver powder optimizes the flow properties of the silver paste and enhances the compactness of the conductive network by increasing the bulk density and reducing the porosity. This structural optimization helps improve the overall performance of the conductive material, ensuring more stable and reliable connections between electronic components.

[0036] In the present invention, the diluent is propylene oxide butyl ether or propylene oxide phenyl ether.

[0037] In the present invention, the accelerator is 2-ethyl-4-methylimidazole.

[0038] In the present invention, the aromatic amine curing agent is MOEA.

[0039] In the present invention, the shear strength of the sintered silver paste material is greater than 55 MPa, preferably 56-69 MPa.

[0040] In the present invention, the volume resistivity of the sintered silver paste material is less than 5×10 -6 Ω·cm, preferably 3.9×10 -6 ~4.8×10 -6 Ω·cm, more preferably 4.0×10 -6 ~4.7×10 -6 Ω·cm.

[0041] The invention also provides a method for preparing a sintered silver paste material, comprising the following steps:

[0042] S1. The flaky silver powder, resin, accelerator and diluent are mixed to obtain a first mixture;

[0043] S2. Grinding the modified PVB and silver particles to obtain a second mixture;

[0044] S3. The first mixture and the second mixture are mixed and filtered to obtain component A.

[0045] In the present invention, the flaky silver powder used in the S1 stage, due to its two-dimensional structure, can effectively fill pores after the addition of main components such as resin. This structural feature enables the formation of a first mixture that not only enhances the mechanical strength of the silver paste but also improves its density after sintering. Next, in the S2 stage, the granular silver powder is pre-dispersed using modified PVB as an organic carrier to form a second mixture. Finally, the first mixture and the second mixture are mixed. This mixing sequence effectively avoids the problem of silver powder agglomeration that may be caused by multiple mixing operations, thereby ensuring the uniformity and performance stability of the sintered silver paste material.

[0046] In S1 and S3, the mixing is performed using a high-speed disperser or a planetary disperser.

[0047] In S1, the mixing speed is 1000-2000 rpm, and the mixing time is 1-5 minutes.

[0048] In S3, the mixing speed is 1500-2000 rpm, and the mixing time is 3-10 minutes.

[0049] In S2, the grinding is performed using a three-roller grinder, and the grinding gap is 15 / 10 μm.

[0050] In S2, the grinding speed is 250 r / s.

[0051] In S3, the mesh size of the filtration is 400 to 500 meshes.

[0052] In the present invention, the sintering temperature of the sintered silver paste material is less than 230°C; preferably, the sintering process is to heat the room temperature to 80-100°C and then keep it warm for 15-25 minutes, heat it to 140-160°C and then keep it warm for 20-30 minutes, and finally heat it to 200°C and keep it warm for 50-80 minutes; wherein the room temperature is 15-25°C.

[0053] On the basis of conforming to the common sense in this field, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.

[0054] Compared with the prior art, the present invention has the following beneficial effects:

[0055] 1. The present invention aims to ensure that the sintered silver paste material has excellent electrical conductivity and dispersion properties, thereby guaranteeing its processing performance, by precisely controlling the ratio and particle size of flaky silver powder and granular silver powder. In terms of resin selection, the present invention adopts bisphenol A epoxy resin and incorporates an appropriate amount of polypropylene glycol diglycidyl ester resin to enhance the elongation and impact resistance of the resin. In addition, the resin can also serve as an active diluent for bifunctional epoxy resin, effectively reducing the viscosity of the resin. In terms of organic carrier, the present invention uses modified polyvinyl alcohol (PVB), whose excellent deformation resistance helps to improve the overall durability of the silver paste material.

[0056] 2. During the preparation process, flaky silver powder is first mixed with resin and other main ingredients to form a first mixture. The flaky silver powder in this mixture effectively fills pores and enhances the material's density. Subsequently, modified PVB is mixed with the granular silver powder as an organic carrier to form a second mixture. By directly mixing the first and second mixtures, silver powder agglomeration, which may occur due to multiple mixing operations, is avoided, thereby ensuring the stability of the sintered silver paste material.

[0057] 3. Due to its unique nano-properties, nano-silver powder's melting point significantly decreases to around 100°C when its particle size reaches the nanometer level. During the sintering process, high temperatures decompose the organic carrier on the surface of the silver powder particles, promoting contact and diffusion between the silver particles, forming sintering necks. These sintering necks form a dense joint. This cross-linking process also creates pores, which buffer the internal stress generated during the expansion and contraction of the joint, resulting in a joint with excellent thermal shock resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 This is the SEM image of the sintered silver paste material prepared in Example 1. DETAILED DESCRIPTION

[0059] To facilitate understanding of the present invention, the present invention will be described more comprehensively and meticulously below in conjunction with preferred embodiments, but the protection scope of the present invention is not limited to the following specific embodiments.

[0060] Unless otherwise defined, all technical terms used hereinafter have the same meanings as those generally understood by those skilled in the art. The technical terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0061] The "ranges" disclosed herein are defined in terms of lower and upper limits. A given range is defined by selecting a lower limit and an upper limit, and the selected lower and upper limits define the boundaries of the particular range. Ranges defined in this manner can be inclusive or exclusive of the end values ​​and can be combined in any manner, i.e., any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60-120 and 80-110 are listed for a particular parameter, it is understood that ranges of 60-110 and 80-120 are also contemplated. Furthermore, if the minimum range values ​​listed are 1 and 2, and if the maximum range values ​​listed are 3, 4, and 5, then the following ranges are all contemplated: 1-3, 1-4, 1-5, 2-3, 2-4, and 2-5. In this disclosure, unless otherwise indicated, the numerical range "ab" is an abbreviation for any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0-5" indicates that all real numbers between "0-5" have been listed herein, and "0-5" is merely an abbreviation for these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0062] Unless otherwise specified, all embodiments and optional embodiments of the present invention can be combined with each other to form new technical solutions.

[0063] Unless otherwise specified, all technical features and optional technical features of the present invention can be combined with each other to form a new technical solution.

[0064] Unless otherwise specified, all steps of the present invention may be performed sequentially or randomly, preferably sequentially. For example, "the method includes steps (a) and (b)" indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, "the method may further include step (c)" indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0065] Unless otherwise specified, the terms "include" and "comprising" used in the present invention may be open-ended or closed-ended. For example, "include" and "comprising" may mean that other components not listed may also be included or that only the listed components are included.

[0066] Unless otherwise specified, the term "or" is inclusive in this disclosure. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied by any of the following conditions: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0067] The raw materials used in the following examples are shown in Table 1.

[0068] Table 1

[0069]

[0070]

[0071] Store component A below -30°C, return to room temperature, and mix with component B in proportion before use.

[0072] The sintered silver paste material of the present invention is sintered under no pressure. The sintering process comprises heating from room temperature to 80-100° C. and then keeping the temperature for 15-25 minutes, heating to 140-160° C. and then keeping the temperature for 20-30 minutes, and finally heating to 200° C. and keeping the temperature for 50-80 minutes.

[0073] Example 1

[0074] 1. Sintered silver paste material of this embodiment:

[0075] The sintered silver paste material consists of component A and component B, and the mass ratio of component A to component B is 100:9.

[0076] Component A includes the following raw materials in parts by weight: 100 parts of silver powder filler, 10.5 parts of resin, 4.8 parts of modified PVB and 0.85 parts of diluent;

[0077] In this embodiment, the silver powder filler includes 20 parts of granular silver powder and 75 parts of flake silver powder;

[0078] In this embodiment, the resin includes 70 parts by mass of bisphenol A epoxy resin (Nan Ya NPEL-127E) and 35 parts of polypropylene glycol diglycidyl ester resin (Dow DER732, USA).

[0079] In this embodiment, the raw materials for preparing the modified PVB are composed of 100 parts of PVB, 24 parts of DOA and 200 parts of DMF, calculated by mass.

[0080] In this embodiment, the diluent is propylene oxide butyl ether;

[0081] The curing agent of component B includes 100 parts of aromatic amine curing agent and 0.5 parts of accelerator;

[0082] In this embodiment, the aromatic amine curing agent is MOEA;

[0083] In this embodiment, the accelerator is 2-ethyl-4-methylimidazole.

[0084] 2. Preparation method of sintered silver paste material of this embodiment:

[0085] (1) Preparation of modified PVB: PVB was dissolved in DMF, and DOA was added. The mixture was heated at 90°C for 25 min, cooled and allowed to stand for 30 min for degassing, and then vacuum dried at 130°C for 5 h to obtain modified PVB.

[0086] (2) Prepare the raw materials according to the above formula.

[0087] (3) Preparation of component A:

[0088] S1. The flaky silver powder, resin, accelerator and diluent were mixed in a high-speed disperser to obtain a first mixture; the stirring speed of the high-speed disperser was 1000 rpm, and the mixing time was 3 min;

[0089] S2. The modified PVB and silver granules were ground twice using a three-roll mill to obtain a second mixture; the grinding gap of the three-roll mill was 15 / 10μm and the grinding speed was 250r / s;

[0090] S3. The first mixture and the second mixture were mixed in a high-speed disperser at 1800 rpm for 8 min, and then filtered through a 400-mesh sieve and degassed to obtain component A.

[0091] Example 2

[0092] The difference between this embodiment and embodiment 1 is that:

[0093] Component A includes the following raw materials in parts by mass: 100 parts of silver powder filler, 8.4 parts of resin, 6.9 parts of modified PVB and 0.51 parts of diluent.

[0094] Other recipes, steps and parameters are the same as in Example 1.

[0095] Example 3

[0096] The difference between this embodiment and embodiment 1 is that:

[0097] In this embodiment, the silver powder filler includes 15 parts of granular silver powder and 75 parts of flake silver powder;

[0098] In this embodiment, the resin includes 70 parts by mass of bisphenol A epoxy resin (Nan Ya NPEL-127E) and 30 parts by mass of polypropylene glycol diglycidyl ester resin (Dow DER732, USA).

[0099] Other recipes, steps and parameters are the same as in Example 1.

[0100] Example 4

[0101] The difference between this embodiment and embodiment 1 is that:

[0102] The bisphenol A epoxy resin in this embodiment is Nan Ya NPEL-127H.

[0103] The diluent in this embodiment is propylene oxide phenyl ether.

[0104] Other recipes, steps and parameters are the same as in Example 1.

[0105] Example 5

[0106] The difference between this embodiment and embodiment 1 is that:

[0107] In this embodiment, the raw materials for preparing the modified PVB are 100 parts of PVB, 18 parts of DEHA and 20 parts of DMF, calculated by mass.

[0108] In this embodiment, the silver powder filler includes 18 parts of granular silver powder and 70 parts of flake silver powder;

[0109] Other recipes, steps and parameters are the same as in Example 1.

[0110] Comparative Example 1

[0111] The difference between this comparative example and Example 1 is:

[0112] In this comparative example, PVB is directly used as the organic carrier without modification.

[0113] Other recipes, steps and parameters are the same as in Example 1.

[0114] Comparative Example 2

[0115] The difference between this comparative example and Example 1 is:

[0116] The PVB used in this comparative example (purchased from Shanghai Macklin) has a butyraldehyde content of 43-50% and a viscosity of 5.0 mPa·s.

[0117] Comparative Example 3

[0118] The difference between this comparative example and Example 1 is:

[0119] The granular silver powder (brand name Metalor) used in this comparative example has a D50 of 5.8 μm and a specific surface area of ​​0.9 m 2 / g.

[0120] Comparative Example 4

[0121] The difference between this comparative example and Example 1 is:

[0122] The preparation method of this comparative example is different from that of Example 1, and the specific steps are as follows:

[0123] S1. The resin, accelerator, diluent and modified PVB were mixed in a high-speed disperser to obtain a first mixture; the stirring speed of the high-speed disperser was 1000 rpm, and the mixing time was 3 min;

[0124] S2. Add silver powder filler (add flaky silver powder and granular silver powder at the same time) to the first mixture, pre-mix it using a stirring paddle, transfer it to a high-speed disperser, evacuate it, mix it at 1200 rpm for 4 minutes, and then filter it through a 400 mesh sieve to obtain component A.

[0125] Effect Examples

[0126] 1. Preparation of analog devices:

[0127] The analog device uses a 30mm×30mm copper plate, printed with the low-temperature sintered silver paste prepared in the above embodiments and comparative examples, with a pattern size of 5mm×5mm square. It is then placed on the silver paste coating and bonded together with a 3mm×3mm silver-plated chip.

[0128] Sintering: heating from 20°C to 80°C and keeping it for 20 minutes, then heating to 150°C and keeping it for 30 minutes, and finally heating to 200°C and keeping it for 60 minutes to obtain a simulated device.

[0129] The SEM image of the sintered silver paste material in Example 1 after sintering is shown in FIG. Figure 1 .

[0130] 2. Performance testing:

[0131] The above-mentioned simulation devices were subjected to performance tests, and the test results are shown in Table 2.

[0132] Table 2

[0133]

[0134]

[0135] (1) The shear strength test method refers to T / CASAS 018-2021 "Shear Strength Test Method for Micro-Nano Metal Sintered Connectors".

[0136] (2) The volume resistivity test is carried out strictly in accordance with the four-wire method, which is achieved by using a high-precision multimeter and a specially designed four-probe test device.

[0137] (3) Test method for high temperature aging retention rate: Test the shear strength of the sintered silver paste material after aging at 250°C for 1000 hours, and calculate the shear strength retention rate.

[0138] (4) The thermal shock test equipment used is the LabCompanion CTS-50 thermal shock test chamber;

[0139] The temperature cycle was set at -40°C to 150°C, with the hot and cold boxes staying for 30 minutes each time. A total of 1000 cycles were performed, and the shear strength retention rate was finally calculated. The specific shear strength (MPa) change data are shown in Table 3 below.

[0140] Table 3

[0141]

[0142] Combining Table 2 and the accompanying drawings, we can see that:

[0143] Comparative Example 1 only uses PVB as an organic carrier without modification, resulting in insufficient impact resistance of the silver paste material. The modified PVB in Comparative Example 2 uses PVB with a low butyraldehyde content as a preparation raw material. Compared with the PVB with a high butyraldehyde content in Example 1, the modification effect is slightly inferior, so the impact resistance of the silver paste is relatively poor. The granular silver powder selected in Comparative Example 3 is different from that in Example 1. The conductive network density is lower and there are more pores, which leads to its poor conductivity. The preparation order of Comparative Example 4 is different from that of Example 1. This different preparation order may cause the silver paste to agglomerate, thereby affecting its conductive properties and mechanical properties, resulting in a decrease in both.

[0144] Unless otherwise specified, all raw materials, reagents, instruments, and equipment used in the present invention can be purchased from the market or prepared by existing methods. The specific embodiments described above further illustrate the purpose, technical solutions, and beneficial effects of the present invention. It should be understood that the above description is only a specific embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included in the scope of protection of the present invention.

Claims

1. A sintered silver paste material, characterized in that: It includes component A and component B; Component A includes the following raw materials in parts by weight: 100 parts of silver powder filler, 5 to 13 parts of resin, 3 to 8 parts of modified PVB, and 0.2 to 2 parts of diluent; Component B includes the following raw materials in parts by weight: 100 parts of aromatic amine curing agent and 0.1 to 1 part of accelerator; The raw materials for preparing the modified PVB include PVB and a modifier, and the modifier is DOA or DEHA; The silver powder filler includes flaky silver powder and granular silver powder.

2. The sintered silver paste material according to claim 1, characterized in that: The mass ratio of the component A to the component B is 100:5-15.

3. The sintered silver paste material according to claim 1, characterized in that: Satisfy at least one of the following conditions ① to ④: ① The modified PVB comprises the following raw materials in parts by weight: 100 parts of PVB and 10 to 35 parts of a modifier; ② The preparation method of the modified PVB is to mix PVB and DOA, heat, degas, and dry; wherein the heating temperature is 85-95° C.; the heating time is 15-30 min; ③ The butyraldehyde group of the PVB is 70-75%; ④ The viscosity of the PVB is 15.0-18.0 mPa·s.

4. The sintered silver paste material according to claim 1, characterized in that: Satisfy at least one of the following conditions ①~②: ① The resin comprises 70 parts by mass of bisphenol A epoxy resin and 20 to 40 parts of polypropylene glycol diglycidyl ester resin; ② In parts by mass, the silver powder filler includes 15 to 35 parts of granular silver powder and 55 to 75 parts of flaky silver powder.

5. The sintered silver paste material according to claim 4, characterized in that: Satisfy at least one of the following conditions ① to ④: ① The viscosity of the bisphenol A epoxy resin is 8000-12000cps; ② The epoxy equivalent of the bisphenol A epoxy resin is 176 to 188 g / eq; ③ The epoxy equivalent of the polypropylene glycol diglycidyl ester resin is 310 to 330 g / eq; ④ The viscosity of the polypropylene glycol diglycidyl ester resin is 55-75 cps.

6. The sintered silver paste material according to claim 4, characterized in that: Satisfy at least one of the following conditions ① to ③: ① The D50 of the flaky silver powder is 1.0 to 4.0 μm; ② The specific surface area of ​​the flaky silver powder is 0.2 to 0.5 m 2 / g; ③ The particle size of the granular silver powder is D50=0.1-0.4 μm.

7. The sintered silver paste material according to claim 1, characterized in that: Satisfy at least one of the following conditions ① to ③: ① The diluent is propylene oxide butyl ether or propylene oxide phenyl ether; ② The accelerator is 2-ethyl-4-methylimidazole; ③The aromatic amine curing agent is MOEA.

8. The sintered silver paste material according to any one of claims 1 to 7, characterized in that: Satisfy at least one of the following conditions ①~②: ① The shear strength of the sintered silver paste material is greater than 55MPa; ②The volume resistivity of the sintered silver paste material is less than 5×10 -6 Ω·cm.

9. The method for preparing a sintered silver paste material according to any one of claims 1 to 7, characterized in that: The following steps are involved: S1. The flaky silver powder, resin, accelerator and diluent are mixed to obtain a first mixture; S2. Grinding the modified PVB and the granular silver powder to obtain a second mixture; S3. The first mixture and the second mixture are mixed and filtered to obtain component A.

10. The method for preparing a sintered silver paste material according to claim 9, characterized in that: Satisfy at least one of the following conditions ① to ⑤: ① In S1 and S3, the mixing is carried out by a high-speed disperser or a planetary disperser; ② In S1, the mixing speed is 1000-2000 rpm, and the mixing time is 1-5 min; ③ In S3, the mixing speed is 1500-2000 rpm, and the mixing time is 3-10 min; ④ The grinding is carried out using a three-roller grinder; ⑤ The mesh number of the filtration is 400 to 500 meshes.